2018
DOI: 10.7150/ijms.23462
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 genetic polymorphisms are biomarkers for the development and progression of breast cancer

Abstract: Breast cancer is a major cause of cancer mortality worldwide. High-mobility group box protein 1 (HMGB1) is a ubiquitous nuclear protein found in all mammal eukaryotic cells that participates in tumor progression, migration and metastasis. HMGB1 overexpression has been indicated in breast cancer patients. However, scant information is available regarding the association between HMGB1 single nucleotide polymorphisms (SNPs) and the risk or prognosis of breast cancer. We report on the association between 4 SNPs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Certain SNPs influence susceptibility to breast cancer [7]. The risk of breast cancer is higher in those carrying the BRCA1 and BRCA2 gene mutations [8,9] and genetic polymorphisms such as high-mobility group box protein 1 (HMGB1) and fascin-1 (FSCN1) [10,11].…”
Section: Ivyspringmentioning
confidence: 99%
“…Certain SNPs influence susceptibility to breast cancer [7]. The risk of breast cancer is higher in those carrying the BRCA1 and BRCA2 gene mutations [8,9] and genetic polymorphisms such as high-mobility group box protein 1 (HMGB1) and fascin-1 (FSCN1) [10,11].…”
Section: Ivyspringmentioning
confidence: 99%
“…10) Recently, many reports have showed that overexpression of extracellular HMGB1 contributed to cancer carcinogenesis and metastasis by promoting apoptotic evasion, mediating tumor-associated inflammation, and increasing tumor cell proliferation, migration and angiogenesis. 16,20,34) Enhanced HMGB1 expression were demonstrated in patients with cancers such as breast cancer, 35) cervical carcinoma, 36) metastatic prostate cancer, 37) and hepatocellular carcinoma. 38) Therefore, antagonizing HMGB1 may be a new target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19) Considering its role as mediator to the progression of tumorigenesis, HMGB1 targeted therapy may be of meaningful value in anti-cancer treatment. 20,21) Given the importance of HMGB1 in tumor initiation and progression, the aim of this study is to investigate whether triptolide could suppress growth of breast cancer by inhibiting HMGB1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP rs1412125 of HMGB1 was selected because the rs1412125 polymorphism was suggested to be associated with pneumonia susceptibility, severity, and inflammatory response [ 42 ]. For HMGB1 rs1360485, patients with one C allele in the rs1360485 domain were suggested to be at greater risk of developing T2 tumors and lymph node metastasis in breast cancer [ 27 ]. The SNP rs1045411 of HMGB1 was selected because it was observed that rs1045411 was correlated with a significant effect on HMGB1 expression, and was significantly associated with clinical outcomes, especially in Chinese gastric cancer patients with aggressive status after surgery [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, HMGB1 was suggested as a novel target for potential therapeutics since highly expressed HMGB1 was found to be associated with the epithelial-to-mesenchymal transition (EMT) and the overexpression of MMP-1, MMP-3, and MMP-10 via the RAGE/NF-κB signaling pathways, facilitating prostate cancer metastasis [ 1 , 16 , 17 , 18 , 19 , 20 ]. Furthermore, polymorphisms of HMGB1 have been associated with many cancers, including oral squamous cell carcinoma (OSCC) [ 21 , 22 ], lung cancer [ 23 , 24 , 25 , 26 ], breast cancer [ 27 , 28 , 29 ], gastric cancer [ 30 ], hepatocellular carcinoma (HCC) [ 31 , 32 ], and colorectal cancer (CRC) [ 33 ], and it was suggested that the SNPs of HMGB1 may provide a potential biomarker for predicting cancer risk, tumor development, or chemotherapy responses [ 21 , 25 , 27 , 31 ]. However, the impact of HMGB1 polymorphisms on prostate cancer susceptibility and clinicopathologic characteristics has remained uninvestigated.…”
Section: Introductionmentioning
confidence: 99%